Assessing the effectiveness of the Kimberley Process in Zimbabwe and the Democratic Republic of Congo - Munemo, Desmond (My University, 2014)
Prior to the establishment of the Kimberley Process in 2003, the global diamond industry, particularly in Africa, was characterised by secrecy, lawlessness, arms trade, money laundering and armed conflict. The system of diamond regulation was ineffective. The Angolan and Sierra Leonean civil wars of 1975 and 1991, respectively, alerted the international community of the role of conflict diamonds in financing rebel movements which were responsible for the outbreak of civil wars in Africa. As a result action had to be taken and it took a combined effort of national governments, non-governmental organizations (NGOs) and the diamond industry to create a global diamond regulatory system known as the Kimberley Process Certification Scheme (KPCS). The objective of this scheme is to break the link between diamonds and conflict. As such, it traces the flow of diamonds from mines to diamond markets through diamond certification process. The effectiveness of the scheme has since been questioned in the case of the Zimbabwean diamonds and the Democratic Republic of Congo where diamond smuggling and trade in conflict diamonds is rife. Diamond situations in these countries have raised questions pertaining to the effectiveness of the Kimberley Process. The K.P. is nevertheless credited for bringing optimism to a global diamond industry which was faced with multi-faceted problems.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, International Relations, 2013